Konseling Individu dengan Teknik Management Stress untuk Meningkatkan Motivasi Kerja Karyawan - Puspasari, Karisma Dewi; Andreani, Vindy (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Decreased work motivation is a psychological problem that employees often experience due to work pressure that is not by their role and capacity. This study aims to determine the effectiveness of individual counseling with stress management techniques in increasing employee work motivation. The subject is an employee who has decreased motivation due to excessive workload. A qualitative approach with a case study design was used in this research. Counseling was conducted in five stages: orientation, exploration, working stage, termination, and follow-up. The results showed that individual counseling with stress management techniques could help the subject identify sources of stress, develop emotion management skills, and build work motivation. Positive changes can be seen from increased work enthusiasm, discipline, and the subject's ability to complete tasks optimally. Stress management-based individual counseling can increase work motivation, especially for employees who experience work pressure. These findings have important implications for developing counseling services in the workplace as a strategy to improve employee well-being and productivity.